Kedudukan Pembayaran Ganti Rugi atas Kelalaian Tenaga Kesehatan yang Mengakibatkan Cacat Permanen dalam Perspektif Pertanggungjawaban Pidana - Stacia Shari Dorie Krisma Waruwu; Muhammad Jufri Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Negligence by healthcare professionals resulting in permanent disability constitutes a form of conduct that may give rise to legal liability under both civil and criminal law. In practice, disputes are often resolved through the payment of compensation to victims as a means of restoring the losses incurred. However, a legal issue arises when such compensation is regarded as a basis for eliminating the criminal liability of healthcare professionals. This study aims to analyze the legal position of compensation payments from the perspective of criminal liability for healthcare professionals whose negligence results in permanent disability to patients. This research employs a normative legal research method using a statutory approach, a conceptual approach, and a case approach. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively. The findings indicate that compensation serves solely as a means of restoring the victim's rights within the scope of civil law and as an implementation of the principle of restorative justice. Such compensation does not extinguish criminal liability because a criminal offense constitutes a violation of the public interest, the enforcement of which falls within the authority of the state. In criminal proceedings, the payment of compensation may only be considered a mitigating circumstance, while criminal prosecution may continue provided that all elements of the offense of negligence have been established.